2014
DOI: 10.1112/blms/bdt104
|View full text |Cite
|
Sign up to set email alerts
|

Division algebras with infinite genus

Abstract: We give an explicit construction of division algebras with infinite genus. We go on to show that there exists a field K for which (1) there are infinitely many nonisomorphic quaternion division algebras with center K, and (2) any two quaternion division algebras with center K are pairwise weakly isomorphic. In fact, we show that there are infinitely many nonisomorphic fields satisfying these two conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…While the latter notion may be useful, some caution needs to be exercised in interpreting its consequences: for example, we don't know whether the fact that the division D and D ′ have the same maximal subfields implies that the matrix algebras M ℓ (D) and M ℓ (D ′ ) have the same maximal subfield /étale subalgebras for any (or even some) ℓ > that the assumption that K is finitely generated is essential as the genus of a division algebra over an infinitely generated field can be infinite, cf. [19], [35].) The proof of Theorem 1.1 also uses the analysis of ramification, but bypasses some technical arguments developed in [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…While the latter notion may be useful, some caution needs to be exercised in interpreting its consequences: for example, we don't know whether the fact that the division D and D ′ have the same maximal subfields implies that the matrix algebras M ℓ (D) and M ℓ (D ′ ) have the same maximal subfield /étale subalgebras for any (or even some) ℓ > that the assumption that K is finitely generated is essential as the genus of a division algebra over an infinitely generated field can be infinite, cf. [19], [35].) The proof of Theorem 1.1 also uses the analysis of ramification, but bypasses some technical arguments developed in [7], [9].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the assumption of finite generation of K is essential for the finiteness of the genus -see [30] and [48] for a construction of division algebras with infinite genus in the general situation.…”
Section: VIII § §1-2])mentioning
confidence: 99%
“…A variation of this problem is concerned only with the consideration of the collection of maximal subfields of algebras. Recently this has been studied by several authors (see [2], [3], [4], [6], [7]). The genus gen(D) of a finite-dimensional central division algebra D over a field F is defined as the collection of classes [D ′ ] ∈ Br(F ), where D ′ is a central division F -algebra having the same maximal subfields as D. This means that D and D ′ have the same degree n, and a field extension K/F of degree n admits an F -embedding K ֒→ D if and only if it admits an F -embedding K ֒→ D ′ .…”
mentioning
confidence: 99%
“…In [6], it is shown that there are quaternion algebras with infinite genus. Besides, it is proved that there exists a field F over which there are infinitely many nonisomorphic quaternion algebras with center F , and any two quaternion division algebras with center F have the same genus.…”
mentioning
confidence: 99%
See 1 more Smart Citation